Pembukuan Sederhana Bagi UMKM - Muttaqien, Fauzan; Cahyaningati, Retno; Rizki, Via Lailatur; Abrori, Imam (UKInstitute, 2022)
The development of the times requires every MSME actor to be more creative in the business implementation process. This activity aims to equip MSME Human Resources (HR) in developing their business, providing information related to business information and entrepreneurial management, facing business competition with competitors and marketing through a mentoring process and simple bookkeeping lessons. Simple bookkeeping training was held at Bohai beach, Binor village, Paiton sub-district, Probolinggo district with a total of 20 participants. The results obtained in this service activity received a positive response from the Probolinggo Regency Cooperatives and Micro Businesses as well as from MSME actors, because they have received knowledge and skills in running their business through simple bookkeeping/recording that is easy to apply, coupled with the provision of simple bookkeeping software incentives. to the participants from the mentors. The implication of PKM activities through simple bookkeeping mentoring for MSMEs is the ability to understand the substance of entrepreneurship by paying attention to good governance, including financial governance by collecting transaction evidence, recording and classifying them systematically so that it is easier for them to know the development of their business. Abstrak: Perkembangan jaman mengharuskan setiap pelaku UMKM untuk semakin kreatif dalam proses pelaksanaan usaha. Kegiatan ini bertujuan untuk membekali Sumber Daya Manusia (SDM) UMKM dalam mengembangkan usahanya, memberikan informasi-informasi terkait dengan informasi bisnis dan manajemen kewirausahaan, menghadapi persaingan bisnis dengan kompetitor serta pemasaran melalui proses mentoring dan pembelajaran pembukuan sederhana. Pelatihan pembukuan sederhana diadakan di pantai Bohai desa Binor kecamatan Paiton Kabupaten Probolinggo dengan jumlah peserta 20 orang. Hasil yang diperoleh dalam kegiatan pengabdian ini mendapat respon yang positif bak dari dinas Koperasi dan Usaha Mikro Kabupaten Probolinggo maupun dari pelaku UMKM, karena telah mendapat pengetahuan dan keterampilan dalam menjalankan usahanya melalui pembukuan/pencatatan sederhana yang mudah diaplikasikan, ditambah dengan pemberian insentif software pembukuan sederhana keapda para peserta dari para mentor. Implikasi dari kegiatan PKM melalui mentoring pembukuan sederhana bagi UMKM adalah adanya kemampuan untuk memahami substansi berwirausaha dengan memperhatikan tata kelola yang baik, diantaranya adalah tata kelola keuangan dengan melakukan pengumpulan bukti transaksi, pencatatan serta menggolongkannya secara sistematis sehingga memudahkannya didalam mengetahui perkembangan usahanya.